Antiquity as a visual battleground: cinema, political uses of the past, and university extension as critical literacy - Furlani, João Carlos (Guará Journal, 2024)
Contemporary historical culture is traversed by a “visual turn” that has shifted the center of gravity of meaning-making about the past from academic writing to screens. Against this backdrop, this article discusses the strategic potential of university extension in mediating between specialized knowledge and cinematic representations of Ancient History. Based on the premise that cinema and television series currently constitute the main source of historical information for the general public (the concept of historiophoty), it argues that the university should not reject these narratives as mere anachronistic falsifications, but treat them as privileged objects of reception analysis. The paper analyzes how iconic productions–from Spartacus and Cold War biblical epics (Ben-Hur, Quo Vadis) to contemporary works like 300 and the series Rome–construct political and religious identities, crystallizing views on the “West,” Christianity, and alterity. Finally, it proposes an extension methodology based on critical visual literacy workshops, aiming to develop the public’s competence to deconstruct the regimes of visuality operating in the public uses of the classical past.
Keywords: Cinema; History; Classical Reception Studies; University Extension; Biblical Epics; Visual Literacy